Inovasi Pembentukan Karakter Anak Berbasis Keagamaan pada Masa Pandemi Covid-19 di Madrasah Diniyah Takmiliyah Awaliyah (DTA) Al Mujahidin Kabupaten Pangandaran - Yayat Hidayat; Ahmad Hapidin; Asep Saepurrohman (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2021)
This study aims to determine the innovations built by the school in the context of building student character through Islamic Religious Education at Al-Mujahidin DTA. This research is a qualitative descriptive study using data collection techniques of observation, interviews, group discussions (FGD) and documentation. The data collection tool used in this study was an interview technique with respondents, namely 97 students, 7 teaching staff, and the parents of the students from DTA Al-Mujahidin. This study uses primary data obtained through observations of activities in the Al-Mujahidin DTA and interviews with students, teachers and parents of students. The results of the study show that the Innovation of Character Education for Children during the Covid-19 Pandemic in Pangandaran Regency includes character values ​​such as respect, responsibility, sharing, perseverance, friendship, cooperation, self-discipline, and honesty must be adjusted empirically for the world of students, the situation is true It is really faced in a straightforward manner, not a problem faced by teachers or parents. Learning will be more meaningful for students if the material has entered in accordance with the stage of reasoning development and provides concrete examples in their environment.